An increase in bed temperature on gasification of dual reactor fluidized bed - Nyoman Suprapta Winaya I; Ketut Gede Wirawan I; Wayan Arya Darma I; Putu Lokantara I; Hartati Rukmi Sari (E3S Web of Conferences, 2018)
One of the main issues using biomass as fuel in air gasification is the dilution of its product gas by the nitrogen in the air. A dual reactor fluidized bed (DRFB) overcomes this problem in which the gasification and combustion reactions are decoupled and conducted in two separate fluidized bed reactors connected by circulating bed material. The DFRB unit made of 304 stainless steel pipe with a height of 100 and 150 cm, and inner diameters (i.d.) of 15.2 and 5.1 cm for gasifier and combustor respectively. The rice husk as fuel and quartz sand as bed material having the same size of 0.4 - 0.6 mm were applied in this investigation. Since the gasification process is an endothermic reaction, gasification temperatures are varied at 600°C to 700°C while combustion reactor were kept at 600°C using the electric heaters enclosed in ceramic cover. The superficial gas velocity in this study was kept constant at 17 m/s using the external air volumetric flux of the blower flow entering the DRFB loop. Gas gasification samples are then examined by gas chromatography to determine syngas content (CO, CH4 and H2). The test results showed that by the increasing temperature of the gasification reactor there was an increase in syngas especially CO gas conentration. The temperature increases in the gasification reactor (600°C, 650°C, 700°C) is able to increase the endothermic reaction in the gasification process which is dominated by CO gas production. The syngas efficiency was found to increase from 40.95% to 43.77%.as the temperature of the gasification reactor increased.